Lithology and Diagenetic Processes of the Baluti Formation (Upper Triassic) from the Amadyia Area, Kurdistan Region, North-Iraq - Shingaly, Waleed S. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Lithologic characteristics and diagenitic processes of the Baluti Formation (Upper Triassic) from two well-exposed sections are studied. The sections are located northwest (Sararu village) and southeast (Sarki village) of Amadyia district, within High Folded Zone, in the Iraqi-Kurdistan. The Baluti Formation consists of intimately interbedded green, gray to black shale and gray limestone with subordinate greenish gray marlstone; those do not alternate in a repeated fashion and are not strictly described as cyclic. Bioclastic limestone, intraclastic limestone, and peloidal limestone interbedded with invasively yellowish-gray shaley mudstone and fissile shale lithologies which are interpreted as slope and basinal units deposited in deeper water. Storms were a dominant factor in initializing down-slope transport from shallower-water settings. Polymictic limestone conglomerate and shallow-water-derived limestone, fossils and siliciclastic grains indicate that depositional slopes were steep enough at times to allow considerable transport from up-slope areas. The bioclastic and peloidal limestones then locally turn into the nodular limestone through early diagenetic modification in deep water. Petrographic evidences indicated that these deposits have undergone both shallow and deep-marine diagenesis with slightly influence of vadose and meteoric diagenesis. Following shallow-marine diagenesis, these intra- and bio-clasts were transported to the deeper part and were exposed to deep-marine water, which appear to have initiated deepmarine diagenesis. The evidence of deep-marine diagenesis is reprecipitation of the small amount of carbonate generated by dissolution of unstable grains (presumably aragonitic) into newly opened molds and partially filled primary pores as clear, fine to medium, equant calcite spar.
Keywords: Lithology,Diagenesis,Baluti Fn,Amadyia,